Library and Information Education in the Digital Age: Students’ Expectations - E. Yu. Kozlenko; N. Yu. Vaytsekhovich (Библиосфера)
In the context of an evolving digital environment of library education, it is important to study the needs and expectations of students as participants of the educational process and the direct consumers of educational services. This paper presents the results of a questionnaire survey of students studying on the specialty “Library and Information Activities” at the Belarusian State University of Culture and Arts. The objective of the survey was to determine the students’ vision of new trends in educational practice and the prospects for the development of library education associated with digitalization. The study was conducted by the working group as a part of the contract research “Explore trends and ways of development of library and information education in the digital age”. The survey touched upon such research areas as a promising vector for the development of library education, students’ readiness for library activities in a digital environment, and the use of information and communication technologies in the learning process. It was found that the students consider the information and technological courses as a promising vector for the development of library education (information courses as the basis for training). In the courses taught at the Faculty of Information and Document Communications, students would like to focus on remote user service, programming, data analytics, digital technologies, neural networks, nanotechnologies, digital marketing, web design basics, the creation and design of electronic resources, the basics of working with graphic editors and other. Assessing the importance of various types of library work in the digital environment, students marked “Working with electronic catalogs and databases” as the most important one. Least of all, students consider themselves ready for the “Work to create electronic information resources” and “Work to provide access to electronic information resources”. In the process of distance learning during the epidemic COVID-19, the greatest difficulty was the increase of the workload, the complication of the learning process. Of less significance were the technical communication problems. А set of measures from the viewpoint of students to improve the quality and competitive advantages of library and information education in the digital age is defined.